Spatial and Epidemiological Analysis of the Incidence of Under-5 Pneumonia in Bangka Belitung - Syariifaturrahmatudzakiyyah; Najmah; Andri Nurtito; Evaluasi; M.Rais Haru; Deby Mahariska; Enni Restiyani (LPPM Universitas Harapan Bangsa, 2024)
Bangka Belitung has the second highest prevalence of pneumonia in Indonesia in 2019 and there will be an increase in cases in 2022. Pneumonia is a disease caused by Streptococcus pneumoniae or pneumococcal bacterial infection which can cause death, especially in developing countries. This research aims to look at the distribution and epidemiology of toddler pneumonia in Bangka Belitung Province in 2023. Using descriptive methods with a quantitative approach using an ecological design with a sample size of 1,157. This research uses secondary data obtained from routine monthly ISPA reports for pneumonia cases, immunization data from the Sehat IndonesiaKu Application (ASIK) and manual recaps, population density data obtained from data listed in the monthly ISPA and BPS Bangka Belitung Province routine reports. The research results show that the Incidence Rate in 2023 is 784.8 per 100,000 children under five with a CFR and UFMR of 0. The highest cases occur in areas with high population density and include low PCV immunization. The proposed cases are 50.6% male and 49.4% female, while the proportion aged < 1 year is 24.2% and 1 - < 5 years is 75.8%. The results of the Chi-Square Test are an age p-value of 0.255 and a gender p-value of 0.960. It was concluded that there was no relationship between the characteristics of toddlers and pneumonia, namely gender and age of toddlers